The prevalence of chronic ankle instability and associated self-reported function in professional ballet dancers in South Africa - Marais, Cherezane (University of the Free State, 2018)
Introduction and aim: Chronic ankle instability (CAI) is characterised by a regular sense of the ankle giving way and recurrent sprains. This condition is thought to arise following acute ankle sprains. Due to a high ankle sprain rate, as well as other sport-specific factors, CAI may be a significant problem in professional ballet dancers. Previous studies have investigated the prevalence of CAI in dancer populations, but no studies have been done on South African dancer populations and none examined the functional impact this condition might have on this population. The aim of this study was to determine the prevalence of CAI, describe the level of associated self-reported function in professional ballet dancers in South Africa and to determine if dancers with CAI differ in respect to ankle injury history, treatment of previous ankle injuries and the presence of pain during functional activities in comparison to dancers who have not developed CAI Methodology: Three professional ballet companies in South Africa were visited by the researcher who supervised the completion of the following questionnaires: the Identification of Functional Ankle Instability Questionnaire (IdFAI); the Foot and Ankle Ability Measure (FAAM); and the Dance Functional Outcome System (DFOS); as well as a self-compiled, literature-based injury history questionnaire. Descriptive statistics, namely frequencies and percentages for categorical data and medians and percentiles for continuous data were calculated. Dancers with/without CAI were associated by means of Fisher’s exact test for categorical data and Kruskal-Wallis test for continuous data. Results: Thirty-three dancers were included. Approximately 76% of the participants reported having sustained at least one significant ankle sprain and 88% of those went on to develop CAI. A total of 67% of participants included in the analysis had CAI. The self-reported function of the participants suffering from CAI was not found to be significantly affected. The median score for dancers who had CAI was 95% on the FAAM (Activities of daily living subscale), 88% on the FAAM (Sport subscale) and 93% on the DFOS. Dancers with CAI demonstrated a tendency to experience more pain in the previously injured ankle during functional activities when compared to dancers who have not developed CAI. Conclusion(s): Although the prevalence of CAI in professional ballet dancers in South Africa was found to be high, their self-reported function was not significantly affected. These findings could stimulate further research to identify possible explanations for the reported level of function despite injury.
Dissertation (M.Sc. (Physiotherapy))--University of the Free State, 2018
Keywords: Ankle -- Wounds and injuries; Sports injuries; Ankle -- Diseases -- Physical therapy; Foot -- Abnormalities; Physiotherapy